Short‐term in vivo modifications of platelet NADPH oxidase 2 (NOX2) and prostaglandin F2α in HIV‐1 patients on abacavir‐based therapies. Issue 10 (November 2016) - Pastori, D; Esposito, A; Carnevale, R; Bartimoccia, S; Nocella, C; Fantauzzi, A; Pignatelli, P; Violi, F; Mezzaroma, I
Abstract : Objectives: The aim of the study was to investigate the in vivo effect of abacavir (ABC) on platelet oxidative stress. Methods: We performed a randomized pilot study including 39 HIV‐1‐infected patients, 17 on zidovudine/lamivudine (ZDV/3TC) and 22 on tenofovir/emtricitabine (TDF/FTC). Ten patients on ZDV/3TC and eight patients on TDF/FTC were randomly allocated to switching the nucleoside backbone to ABC/3TC. At baseline and after 6 months, platelet oxidative stress was assessed by platelet NADPH oxidase 2 (NOX2)‐derived peptide (sNOX2‐dp), a marker of NOX2 activation, and platelet prostaglandin F2α (8‐iso‐PGF2α ). Platelet activation was measured by soluble CD40L (sCD40L). Results: At baseline, no differences between ZDV/3TC or TDF/FTC recipients were found. After 6 months, patients switching from ZDV/3TC showed a decrease of sNOX2‐dp (from 20.9±5.7 to 12.5±3.8 pg/ml, p=0.002) and 8‐iso‐PGF2α (from 154.3±41.9 to 122.9±28.0 pmol/l, p=0.025). No effects on platelet oxidative stress biomarkers were observed in subjects from TDF/FTC, who showed a significant increase in blood glucose (p=0.043) and total cholesterol (p=0.027). ABC showed no effect on sCD40L levels in both groups. Conclusions: ABC reduced platelet sNOX2‐dp and 8‐iso‐PGF2α in HIV‐1 subjects switching from ZDV/3TC but not in those from TDF/FTC after 6 months. No changes in platelet activation were found in both groups.